THE EFFECT OF FLASH SALES AND FREE SHIPPING VOUCHERS ON PURCHASING DECISIONS IN SHOPEE E-COMMERCE - Raisa Natasya Devianti; Mujtabah Faturrurahman; Verus Hardian (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to determine the extent to which flash sales and free shipping vouchers influence purchasing decisions in Shopee e-commerce. This research employed a quantitative approach using a questionnaire distribution method. The population consisted of 99 Shopee users who had conducted purchasing transactions through the application. The results of the multiple linear regression analysis produced the equation: Y = 12.197 + 0.760(X1) + 0.447(X2). The hypothesis testing results indicate that flash sales and free shipping vouchers significantly affect purchasing decisions, with a significance value of Sig < 0.001 < 0.05, therefore H0 is rejected and H1 is accepted. The coefficient of determination value (Adjusted R Square) was 0.614, indicating that the variables of flash sales and free shipping vouchers explain 61.4% of the variation in purchasing decisions on Shopee e-commerce, while the remaining 38.6% is influenced by other variables not examined in this study.